2002
DOI: 10.1105/tpc.010391
|View full text |Cite
|
Sign up to set email alerts
|

KNAT1 and ERECTA Regulate Inflorescence Architecture in Arabidopsis

Abstract: Plant architecture is dictated by morphogenetic factors that specify the number and symmetry of lateral organs as well as their positions relative to the primary axis. Mutants defective in the patterning of leaves and floral organs have provided new insights on the signaling pathways involved, but there is comparatively little information regarding aspects of the patterning of stems, which play a dominant role in architecture. To this end, we have characterized five alleles of the brevipedicellus mutant of Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
180
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 34 publications
12
180
0
Order By: Relevance
“…Our results strongly indicate that all KNOX and BELL proteins recognize the same DNA-binding motif; however, genetic and molecular evidence in Arabidopsis suggests that STM and KNAT1 control different developmental pathways (3,4,47). Even if there is functional overlap between these two knox genes, it is difficult to explain how they control different pathways (i.e., target genes) yet bind to the same DNA sequence.…”
Section: Discussionmentioning
confidence: 49%
“…Our results strongly indicate that all KNOX and BELL proteins recognize the same DNA-binding motif; however, genetic and molecular evidence in Arabidopsis suggests that STM and KNAT1 control different developmental pathways (3,4,47). Even if there is functional overlap between these two knox genes, it is difficult to explain how they control different pathways (i.e., target genes) yet bind to the same DNA sequence.…”
Section: Discussionmentioning
confidence: 49%
“…It has been suggested that coordinated cell division and differentiation in plant SAMs is controlled by different classes of receptor kinases (Dievart and Clark 2004;Shiu et al 2004) that include the CLV family of proteins (Stahl and Simon 2005) and ERECTA (Torii et al 1996;Laufs et al 1998;Yokoyama et al 1998;Douglas et al 2002;Shpak et al 2003;Woodward et al 2005). The Clavata1-like protein Gma.7646.1.A1_at was up-regulated in the soybean SAM and we found that the most similar Arabidopsis orthologue of this gene was AT5G51560, which is annotated as encoding leucine-rich transmembrane protein kinase.…”
Section: Receptor Kinases and Cell Signallingmentioning
confidence: 89%
“…It was proposed that KNAT1 and ER are required to restrict the action of an asymmetrically localized, vasculature-associated chlorenchyma repressor at the nodes, and that ER functions redundantly with KNAT1 to influence plant architecture and stem differentiation (Douglas et al 2002). Although our previous results showed that ER plays an important role in leaf polarity formation, very little is known about the physiological function of ER in the AS1/AS2 regulatory pathway.…”
Section: Introductionmentioning
confidence: 97%